Mastering the Body: Reading a Discourse of Embodiment in the Zhuangzi - Ko, Lana (Religion compass, 2025)
The Zhuangzi is one of the most well-known early Chinese classics. Subversive and iconoclastic, both in terms of its subject matter and narrative style, the text has profoundly influenced the intellectual and literary history of East Asia. First introduced to the West in the late nineteenth century as an early "Daoist" classic, the Zhuangzi has become a popular and widely read text within Western academia, from Sinology to comparative philosophy and religion. Rather than providing a comprehensive literature review on studies of the Zhuangzi, this paper will maintain a narrow focus, confining its attention to a specific theme: skill mastery. The text features many stories of fantastic masters who have acquired wonderful techniques, such as butchering, swimming, or making bells. In recent decades, these stories have drawn significant attention from Western scholarship, and scholars have shown the narrative's multifaceted nature by reading the stories from various perspectives. The first part of the paper will examine previous studies on the narrative of skill mastery in the Zhuangzi. Having summarized their analytic frameworks, the paper then moves to the second part, presenting an original argument: the skill stories and other stories about self-cultivation in the Zhuangzi can be read together as a coherent discourse of mastering the body. The paper envisages five successive stages of learning techniques and mastering the body by interweaving the stories scattered throughout the text. Examination of the five stages will make clear that the central focus of the discourse is on the holistic body as one self: the physical body, the heart, qi, and the spirit all work together in harmony. The discourse will also reveal that mastery of the body addresses the issues of death. The paper will conclude that the discourse of mastering the body in the Zhuangzi showcases a unique philosophy of embodiment in early China for its aim of transcendence.